Experimental analysis of the performance of a new shipboard gravity gradient measurement system - Rui Li; Da Li; Qing Shu; Zhenyu Fan; Kai Lu; Jianxin Zhou; Jiahong Zhang; Guangjing Xu (Frontiers in Physics, 2023)
The gravity gradient tensor, which has a higher resolution than gravity, is used in a variety of fields, including the discovery of energy resources, auxiliary navigation, and national defense building. Our team has achieved significant advancements in various essential technologies, such as high-resolution accelerometers, and has constructed China’s first self-controllable shipboard gravity gradient measurement system. In the laboratory, accuracy is determined using the mass gravitation technique, static test accuracy of Tuv and Txy is 7.22 E and 3.58 E, while dynamic test accuracy of Tuv and Txy is 9.09 E and 4.16 E. For outfield shipborne test measurement, the internal accord accuracy of Tuv and Txy of the repeat line is 28.2E@750m and 28.8E@750m, and that of the intersection point is 28.2E@750m and 26.8E@750m. The performance of the system is completely validated by dynamic and static testing, laying the groundwork for the practical implementation of gravity gradient technology.